Optimizing Binmas Unit Counseling in Preventing Fraud Crimes at Ciamis Police - Adinata, Fabian Yafi (Advances in Police Science Research Journal, 2024)
In the last 4 years, fraud is the most common case in the jurisdiction of the Ciamis District Police with 463 cases. The binmas unit has a role in efforts to tackle fraud cases by counseling. This study aims to analyze and explain the implementation, the ability of officers, and the factors that influence the implementation of Binmas unit counseling. The location of the study was at the Ciamis Regional police station with a focus on Binmas. This study uses qualitative methods with descriptive analysis techniques. Using data triangulation (Moleong; 2006: 330) 4 (four) kinds of techniques namely sources, theories and techniques as well as primary and secondary data sources. Data validity is data reduction, data display and conclusion drawing. This research uses the principles of management principles, the theory of law enforcement and the theory of Force Field Analysis as well as the optimization concept, the concept of counseling, the management concept of implementing counseling and the concept of fraud. The implementation of counseling that is not maximally carried out by the Binmas unit is analyzed from the functions of planning, organizing, managing resources, communicating, directing, motivating, and controlling as well as the officers' ability to conduct counseling. In the implementation of penyuluhan, there are internal factors that influence are other functions, budget, infrastructure and human resources. External factors that influence are the formulation of fraudulent criminal acts, the condition of the Ciamis district police jurisdiction, collaboration with other agencies, and Perkap No. 21 of 2007. In conclusion, the inhibiting factors of counseling conducted by the Ciamis Regional Police Binmas Unit are human resources, facilities and infrastructure, formulation fraud, and the condition of the Ciamis district police jurisdiction.